PENGARUH KURS RUPIAH, INFLASI, DAN HARGA MINYAK DUNIA TERHADAP INDEKS HARGA SAHAM PERUSAHAAN TRANSPORTASI DAN LOGISTIK (IDXTRANS) - Gaswira, Leni; Meutia, Tuti; Harahap, Ainul Yusna (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2025)
This study aims too examine the effect of the rupiah exchange rate, inflation, and world oil prices on the Stock Price Indeks of the Tranportation and Logistic Sector (IDXTRANS). This is a quantitative research using secondary data consisting of 47. The data were selected using a saturated sampling technique and analyzed using SPSS. The analytical methods used include descriptive statistics, classical assumption tests, and hypothesis testing through multiple linear regression analysis. The results of the study show that: (1) the rupiah exchange rate has a negative and significant effect on IDXTRANS; (2) inflation has a positive and significant effect on IDXTRANS; (3) word oil prices also have a positive and significant effect on IDXTRANS; and (4) simultaneously, the variables of rupiah exchange rate, inflation, and world oil prices significantly effect IDXTRANS. This study is limited to a specific sector and time, and does not include other potential macroeconomic or political factors. Future research is recommended to use a longer observation period and to include additional variables such as interest rates, political stability, and consumer confidence index to obtain more comprehensive results.